Automated Periotome versus Conventional Periotome in Intra-Alveolar Extraction of Sheep Jaw: An In Vitro Study - Sam Thomas Kuriadom; Sarmad Al-Chalabi; Karrar M. H. Hadi; Ashraf M. Ishbair (Hindawi Limited, 2022)
Background. Atraumatic dental extraction is the way forward in modern dentistry. This study aims to compare the effectiveness of automated periotome with conventional periotome with regard to operating time, postoperative gingival laceration, and bone and tooth structure fractures. Methods. This is an in vitro study of forty posterior teeth of sheep mandibles. Ten sound healthy mandibles were selected, and each mandible was then divided into two quadrants with two teeth in each quadrant. Teeth were then extracted by conventional periotome for the first group (one quadrant) and by automated periotome for the second group (other quadrants). A statistically significant P value is set at below 0.05 with a 95% confidence interval. Results. No bone fracture was seen in any of the cases of automated periotome with a significance of 0.004 when compared to the fractures seen in seven cases in the conventional group. Whereas comparing the other parameters among the different groups did not show any significant difference. Conclusion. It is worthwhile to use the automated periotome in simple extractions, especially when implants are considered in the treatment plan.